Analisis Pola Iringan Gambang dalam Kesenian Tembang Sunda Pagerageungan - Chandra Nur Fauzi; Denden Setiaji; Arni Apriani (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Sundanese song pagerageungan is a traditional art originating from Tasikmalaya district. The xylophone accompaniment pattern in the Sundanese song art Pagerageungan plays a very important role in creating an atmosphere and strengthening the message contained in the song lyrics. The xylophone, as a traditional Sundanese instrument made from wooden blades, produces a distinctive sound and has a dual function as a rhythm regulator as well as adding melodic nuances to the song. The xylophone accompaniment pattern in this song is not only rhythmic, but also often has a melodic character that beautifies the song's strains. This gambang accompaniment pattern has 3 parts, namely merean, cacagan and geumbyang. The aims of this research are: (1) to find out the xylophone accompaniment pattern in the Sundanese pagerageungan song art (2) to find out the function of the xylophone accompaniment pattern in the Pagerageungan Sundanese song art. The method used in this research is qualitative with a descriptive analysis approach. The techniques used in this research are observation, interview and documentation techniques. The main instrument in this research is the research itself using tools in the form of field notes and recording tools in the form of cellphones.